PELAKSANAAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN KUBU RAYA DALAM PEMBENTUKAN PERATURAN DAERAH - NIM. A01109161, HUSNUL KHATIMAH (Jurnal Fatwa Hukum, 2023)
Abstrac Based on the background described previously, the problem that will be discussed is how to implement the Legislative function of the Kubu Raya Regency DPRD in the Formation of Regional Regulations for the 2015-2016 Period. More specifically, this research explains what factors hinder the implementation of the DPRD's functions in forming regional regulations. This research aims to determine the implementation of the Legislative function of the Kubu Raya Regency DPRD in the Formation of Regional Regulations and to find out the factors that hinder the effectiveness of the implementation of the Legislative function of the Kubu Raya Regency DPRD in making Regional Regulations. To discuss this, this research uses qualitative methods with interview instruments with one one member of the Kubu Raya Regency DPRD and document study for data collection in the form of an attachment to the Kubu Raya Regency DPRD work program for the 2015-2016 period, an attachment to the 2015-2016 regional regulation formation program. The findings in this research are that the performance of the Kubu Raya Regency DPRD for the 2015-2016 period in implementing legislative functions is still not optimal. This can be seen from the implementation of the legislative function in the preparation/drafting and discussion of the Draft Regional Regulation.Based on the results of research and discussion, the implementation of the Legislative function of the Kubu Raya Regency DPRD 2015-2016, there are several factors inhibiting the implementation of the Legislative function of the Kubu Raya Regency DPRD in Making Regional Regulations, namely Time Limitations in discussing the Draft Regional Regulation, Infrastructure, namely insufficient expert staff to formulate the draft Regional Regulation and mechanisms. coordination, communication and cooperation between government agencies in the process and procedures stages of drafting the Draft Regional Regulation.Keywords: Legislation, Function, Regional Regulationsi Abstrak Berdasarkan latar belakang yang telah diuraikan sebelumnya maka permasalahan yang akan dibahas adalah bagaimana pelaksanaan fungsi Legislasi DPRD Kabupaten Kubu Raya Dalam Pembentukan Peraturan Daerah Periode 2015-2016. Lebih khusus penelitian ini menjelaskan faktor-faktor apa saja yang menghambat pelaksanaan fungsi DPRD dalam pembentukan Peraturan Daerah tersebut. Penelitian ini bertujuan untuk mengetahui pelaksanan fungsi Legislasi DPRD Kabupaten Kubu Raya Dalam Pembentukan Peraturan Daerah dan untuk mengetahui faktor-faktor yang menghambat efektifitas pelaksanaan fungsi Legislasi DPRD Kabupaten Kubu Raya dalam pembuatan Peraturan Daerah.Untuk membahasnya, penelitian ini menggunakan metode kualitatif dengan instrumen wawancara dengan salah satu anggota DPRD Kabupaten Kubu Raya dan studi dokumen untuk pengumpulan data berupa lampiran program kerja DPRD Kabupaten Kubu Raya periode 2015-2016, lampiran program pembentukan peraturan daerah 2015-2016. Temuan dalam penelitian ini adalah kinerja DPRD Kabupaten Kubu Raya periode 2015-2016 dalam pelaksanaan fungsi legislasi masih belum optimal. Hal ini dapat dilihat dari pelaksanaan fungsi legislasi dalam penyiapan/penyusuan dan pembahasan Raperda.Berdasarkan hasil penelitian dan pembahasan bahwa pelaksanaan fungsi Legislasi DPRD Kabupaten Kubu Raya 2015-2016 terdapat beberapa faktor penghambat pelaksanaan fungsi Legislasi DPRD Kabupaten Kubu Raya Dalam Pembuatan Perda yaitu Keterbatasan Waktu dalam pembahasan Raperda, Sarana Prasaran yaitu tenaga ahli yang kurang untuk merumuskan naskah raperda serta mekanisme koordinasi, komunikasi dan kerjasama antar instansi pemerintah dalam tahapan proses dan prosedur penyusunan Raperda.Kata Kunci: Legislasi, Fungsi ,Peraturan Daerah